#TITLE_ALTERNATIVE# - HADI (NIM 122 04 038), SYAFRAN
Bottom Hole Assembly are combination of under surface tools that installed at drill string so we can get a good performance when we make a slope or direction at well trajectory. The presence of build up and horizontal section in a horizontal well drilling cause some problems that related to the movement and the loading of string. The more length of the horizontal section will decrease tension load and will increase torsion as well as drag force. It is necesarry to consider the critical buckling force in order to avoid the buckling of the string. According to the problems mentioned above, there are several factors that affect the force on horizontal drilling. They are friction between drillstring and the well bore, the geometry of the well, the stress on the pipe, the presence of build up section and the bouyancy of the drilling mud. These factors effect to each other. By using simple mathematical model, the magnitude of the load on the assembly can be calculated. Consist of the torsion, drag and buckling force as well as the hookload. Therefore, it is possible to design the proper assembly of the string in order to reach lateral section optimally.